La Política Europea de Cooperación para el Desarrollo: examen de la presidencia española (primer semestre de 2002) - Sotillo Lorenzo, José Ángel (Revista Española de Desarrollo y Cooperación, 2023)
The article focuses on the Development Assistance Policy carried out during the Spanish Presidency of the European Union. It aims at describing, analyzing and examining the main achievements obtained by the Spanish Goverment during the six— months Presidency.